Temperature-Controlled Radiofrequency Ablation for Pulmonary Vein Isolation in Patients With Atrial Fibrillation - Iwasawa, Jin; Koruth, Jacob S; Petru, Jan; Dujka, Libor; Kralovec, Stepan; Mzourkova, Katerina; Dukkipati, Srinivas R; Neuzil, Petr; Reddy, Vivek Y (Journal of the American College of Cardiology, 2017)
BACKGROUND: Saline irrigation improved the safety of radiofrequency (RF) ablation, but the thermal feedback for energy titration is absent. OBJECTIVES: To allow temperature-controlled irrigated ablation, a novel irrigated RF catheter was designed with a diamond-embedded tip (for rapid cooling) and 6 surface thermocouples to reflect tissue temperature. High-resolution electrograms (EGMs) from the split-tip electrode allowed rapid lesion assessment. The authors evaluated the preclinical and clinical performance of this catheter for pulmonary vein (PV) isolation. METHODS: Using the DiamondTemp (DT) catheter, pigs (n = 6) underwent discrete atrial ablation in a temperature control mode (60°C/50 W) until there was ∼80% EGM amplitude reduction. In a single-center clinical feasibility study, 35 patients underwent PV isolation with the DT catheter (study group); patients were planned for PV remapping after 3 months, regardless of symptomatology. A control group included 35 patients who underwent PV isolation with a standard force-sensing catheter. RESULTS: Porcine lesion histology revealed transmurality in 51 of 55 lesions (92.7%). In patients, all PVs were successfully isolated; no char or thrombus formation was observed. Compared with the control group, the study cohort had shorter mean RF application duration (26.3 ± 5.2 min vs. 89.2 ± 27.2 min; p < 0.001), shorter mean fluoroscopic time (11.2 ± 8.5 min vs. 19.5 ± 6.8 min; p < 0.001), and lower acute dormant PV reconduction (0 of 35 vs. 5 of 35; p = 0.024). At 3 months, 23 patients underwent remapping: 39 of 46 PV pairs (84.8%) remained durably isolated in 17 of these patients (73.9%). CONCLUSIONS: This first-in-human series demonstrated that temperature-controlled irrigated ablation produced rapid, efficient, and durable PV isolation. (ACT DiamondTemp Temperature-Controlled and Contact Sensing RF Ablation Clinical Trial for Atrial Fibrillation [TRAC-AF]; NCT02821351).
Keywords: výsledek terapie; Young Adult; prasata; electrogram; Swine; Temperature; Electrocardiography; Male; Middle Aged; remapping; mladý dospělý; Equipment Design; následné studie; Adolescent; Heart Conduction System; catheter ablation; Adult; Aged; dospělí; Prospective Studies; mužské pohlaví; senioři; Catheter Ablation; design vybavení; mladiství; Follow-Up Studies; Atrial Fibrillation; Pulmonary Veins; Time Factors; Treatment Outcome; Animals; lidé; převodní systém srdeční; ženské pohlaví; Humans; zvířata; časové faktory; histology; venae pulmonales; teplota; katetrizační ablace; Female; first-in-human; lidé středního věku; fibrilace síní; elektrokardiografie; prospektivní studie